Editorial: How in the world are we handling COVID‐19? - Dubicka, Bernadka (Child Adolesc Ment Health, 2020)
These are not normal times. As an editorial team, we felt that there was an urgency to reflect on our global experiences of the COVID‐19 pandemic with our international colleagues. Instead of our planned debate series, we therefore commissioned a series of reflections on the impact of the pandemic on child and adolescent mental health throughout the world. We hope that you will find these reflections informative, thought‐provoking, and in some cases, inspirational.